P5.034 British Co-Operative Clinical Group (BCCG) Project - How Often Are Men Who Have Sex with Men (MSM) Advised to Attend For Repeat Sexual Health Screening in the UK?. (13th July 2013) - Clarke, E; Shone, E; Broad, C; Baker, A; Patel, R; Rowen, D
Abstract : Background: Within the UK rates of HIV, STIs, and sexual risk taking behaviours are increasing in MSM. 24% of new UK HIV diagnoses in MSM are recently acquired. Increased frequency of sexual health screening could reduce transmission of STIs, and this policy is advocated in Australia and America. UK guidelines are vague, advising increased screening for MSM with risk taking behaviours but without specifying frequency or behaviours. Aim: to assess what advice UK clinics give MSM about how frequently they should receive sexual health screening, and how this varies with risk taking behaviours. Methods: BCCG members representing UK level 3 sexual health clinics were asked to complete an online survey assessing how often they would advise MSM with different patterns of risk taking behaviours to attend for screening. Results: 53 clinics responded. 53% had local guidance on screening frequency, with 89% based on national guidelines. 94% BCCG members and 59% local guidelines identified behaviours requiring increased screening frequency. The majority (53–66%) advised 3 monthly screening for MSM with over 10 partners in the last 6 months, attending sex on premises venues, using recreational drugs during sex, using the Internet to find partners, participating in group sex, or being HIV positive and sexually active. 32% and 40% respectively recommended 6 monthly screening for sexually active MSM and for those who had unprotected anal sex in the last 12 months. Discussion: Whilst the majority of clinics surveyed would recommend 3–6 monthly screening for MSM with risk taking behaviours, this varies with many clinics providing no specific advice on screening frequency. Clear UK guidance is needed to respond to the HIV epidemic in MSM by promoting early diagnosis of incident infection, and to ensure that efforts to contain costs through service contraction do not impinge on access or screening for this important group.